Soundscape - Interactive Data Visualisations of Spotify’s Top Songs - Espejo, Abigail (Wellington Faculty of Engineering Symposium, 2023)
The availability of complex and diverse data has highlighted the need for effective data representation and analysis techniques. In this context, the project addressed the challenge of exploring rich music ranking data by developing an interactive visualisation web application. By leveraging the audio characteristics of the top 2,000 Spotify tracks spanning 1999 to 2019, the project will utilise React.js to create a web- application, while employing tools provided by the D3.js library for dynamic and interactive visualisations. An integral part of the project involved conducting a user study to evaluate users’ perception, interaction, and cognitive reasoning within the visualisations. The outcome of the project is a web-based interactive visualisation system that empowers users to gain deeper insights into the music ranking data, enabling effective data exploration and informed decision-making. The system’s effectiveness and usability were rigorously assessed through the user study, ensuring it meets the requirements and expectations of the intended users.